Strengthening Synergy Of Mangrove Ecosystem Management Based On Blue Carbon Ecosystem In Setiu Wetland Terengganu Darul Iman Malaysia - Hakim, Arif Rahman; Sulaiman, Sabri Bin; Zulherawan, M.; Fadillah, M. Arsya; Azmi, M. Alga Viqky (Doctoral Program of Social Science, Pasundan University, 2025)
Blue carbon ecosystems (Mangroves, Seagrass and Brackish Swamps) have a relatively small area compared to the ocean and other ecosystems. Coastal areas that are transitional between land and sea ecosystems are areas that are vulnerable to various types of changes, both on land and at sea. The mangrove ecosystem is one of the ecosystems in coastal areas that plays an important role in the sustainability of life for biota that live in coastal areas. The mangrove ecosystem has various very complex functions both ecologically and economically and socially. Management of the mangrove ecosystem in Setiu Wetland Terengganu Malaysia with an area of ??1,574 ha which is currently known as the Setiu Wetland State Park is managed by a group of local volunteers. Management also collaborates with government agencies, non-governmental organizations and higher education institutions that have transformed the Setiu wetland area over the past two decades. The existence of mangroves is encouraged to become a conservation area along the coastline filled with fishing villages along the coastline. Improved management continues to be pursued to preserve the park's biodiversity and highlight its tourism attractions according to the Setiu District Regional Plan 2035.